Determinan Produktivitas Tenaga Kerja Berdasarkan Provinsi di Indonesia - Larasari, Nadia Putri; Anis, Ali (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This study aims to determine the effect of education, wages, and technology on labor productivity in Indonesia. This study uses secondary data sourced from the Central Bureau of Statistics of Indonesia. With research variables grouped into two parts, namely, the dependent variable using labor productivity with the indicator of GRDP at Constant Prices per number of working population. Independent variables consisting of education with an indicator of average length of schooling, wages with an indicator of average wages per hour of workers, and technology with an indicator of the percentage of households that have accessed the internet in the last 3 months. This study uses a panel data regression analysis method with the selected model being the Fixed Effect Model (FEM) with a cross section of 34 provinces in Indonesia and a time series of 2013-2022. The results of the study show that education has a positive and significant relationship with labor productivity. Wages have a positive and insignificant relationship with labor productivity. And technology has a positive and significant relationship with labor productivity.